Analisis wewenang Mahkamah Konstitusi terhadap penyelesaian sengketa kewenangan lembaga negara - Hasanah, Siti Inayatul (Maliki Interdisciplinary Journal, 2024)
Various independent commissions and institutions were established after the 1945 Constitutional Amendment. These State Institutions were established with equal position and have the authority or responsibility to supervise each other and carry out their respective obligations (Check and Balance). Disputes between State Institutions can occur because the division of State Institutions based on their functions and authorities can lead to disputes between them. This research uses normative juridical research methodology, this writing aims to find out more about the role of the Constitutional Court when handling and resolving disputes over authority between state institutions. In this case, the Constitutional Court is authorized to hear, and give decisions on power disputes that occur between state institutions.